Overview of hydrogen economy in Australia. Issue 1 (5th August 2022) - Kar, Sanjay Kumar; Sinha, Akhoury Sudhir Kumar; Bansal, Rohit; Shabani, Bahman; Harichandan, Sidhartha
Abstract: The hydrogen economy is on the verge of expansion across the globe. Leading economies like Japan, South Korea, China, the United States of America, Germany, and Australia are steadily pushing for greater hydrogen integration into their energy systems. Australia's thrust on the hydrogen economy becomes prominent with clear strategic actions to enhance clean technology‐based hydrogen production. The paper critically analyses Australia's strategies and policies to expand its hydrogen economy. The paper found that Australia fixed ambitious targets to increase hydrogen penetration in the domestic market and export to Japan, China, and South Korea. Australia's national hydrogen strategy emphasized creating a strong hydrogen value chain to capitalize on abundant renewable resources. This article affirms that Australia has enormous potential for cost‐competitive green hydrogen production and export. Australia's cost‐competitive green hydrogen production with modern supply chain infrastructure will offer competitive advantages over the other exporters. States/regions are trying to align their hydrogen policies and strategies along the lines of the national strategy. However, some concerns demand timely attention from the stakeholders. Australia should address multiple challenges, including a lack of investment, lower public awareness, and insufficient infrastructure to push hydrogen adoption in the domestic market. Further, Australia must utilize its strengths to take advantage of the emerging hydrogen markets in Japan, China, and South Korea. This article is categorized under: Sustainable Energy > Other Renewables Emerging Technologies > Hydrogen and Fuel Cells Policy and Economics > Regional and International Strategies Abstract : Australia's booming hydrogen economy.